Mengubah Kelemahan Menjadi Kekuatan: Memantik Kepekaan dan Budaya Baru Pengelolaan Sampah pada Kaum Muda - Derajad Sulistyo Widhyharto; Elvin Wahyu Wardhana; Stefanus Fajar Setyawan (Jurnal Pengabdian, Riset, Kreativitas, Inovasi, dan Teknologi Tepat Guna, 2023)
Ineffective waste management in the Special Region of Yogyakarta, coupled with weak community involvement, has led to protests and the closure of the Integrated Waste Management Facility (TPST). The government is actively seeking solutions by allocating specific land, fostering interregional cooperation, and providing waste sorting facilities for the public. However, waste management appears to be trapped in a vicious cycle due to the neglect of the community's role as a key stakeholder. This article bridges the gap between circular economy knowledge and waste management practices through youth involvement. The Youth Studies Center at Gadjah Mada University collaborates with entities such as Bank Sampah Tinalan, Daur Resik, Sawo Kecik, and DNVB Indonesia, engaging students from SMP Negeri 9 and SMA Negeri 5 in Yogyakarta in a campaign titled "Pilah.id." Using the action research method supported by the UGM DPkM 2021/2022 Community Service Grant, this program engages students from SMPN 9 and SMAN 5 Yogyakarta in self-managing waste. Post-action research surveys revealed that 85.7% of students actively engage in waste management after participating in the Pilah.id program, with 75% of them not utilizing local waste banks. While participants demonstrate a strong understanding of waste sorting, their involvement in local waste banks remains limited, highlighting the need for increased support and capacity building for these local waste banks.